Averting catastrophic climate change: confronting wealth. (4th December 2007) - Hurth, Victoria; Wells, Peter
In the context of potential catastrophic climate change, it is vital that fundamental drivers of carbon dioxide emissions are pinpointed and addressed. One of the key drivers of these emissions is shown to be increased economic wealth. This paper highlights that links between wealth and carbon dioxide must be addressed, and that although highly debated, the links are not well considered, especially at the detailed level of what drives consumption preferences of the global wealthy. In the context of increasing wealth concentration and poverty gaps, this subject is central to issues of social justice as well as environmental integrity.